1998
DOI: 10.1089/end.1998.12.9
|View full text |Cite
|
Sign up to set email alerts
|

Redistribution of Renal Blood Flow after SWL Evaluated by Gd-DTPA-Enhanced Magnetic Resonance Imaging

Abstract: Extracorporeal shockwave lithotripsy (SWL) is currently accepted as an effective noninvasive treatment for a wide variety of urinary tract calculi. However, the bioeffects of high-energy shockwaves on renal parenchyma have yet to be fully elucidated. The objective of this study was to measure the acute changes in regional renal hemodynamics associated with SWL utilizing dynamic gadolinium-DTPA-enhanced magnetic resonance imaging (MRI). Seven patients who underwent SWL for renal calculi had an MRI study within … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 20 publications
0
14
0
Order By: Relevance
“…4,25,26 Several clinical studies, measuring renal resistive index or followed renal blood velocity in the kidney subjected to SWT, showed that an increase in resistive index or a reduction in blood velocity indicative of vasoconstriction occurred. 4,5,27 It has also been reported that there is a decrease in renal perfusion in kidney following SWT procedure by using dynamic gadolinium-DTPA enhanced magnetic resonance imaging. 27 Studies focused on two possible explanations for the impairment of renal flow; renal sympathetic nerves may be activated by shock waves and vasoconstriction may be occurred by vasoconstrictors released from kidneys in response to the shock waves.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…4,25,26 Several clinical studies, measuring renal resistive index or followed renal blood velocity in the kidney subjected to SWT, showed that an increase in resistive index or a reduction in blood velocity indicative of vasoconstriction occurred. 4,5,27 It has also been reported that there is a decrease in renal perfusion in kidney following SWT procedure by using dynamic gadolinium-DTPA enhanced magnetic resonance imaging. 27 Studies focused on two possible explanations for the impairment of renal flow; renal sympathetic nerves may be activated by shock waves and vasoconstriction may be occurred by vasoconstrictors released from kidneys in response to the shock waves.…”
Section: Discussionmentioning
confidence: 98%
“…4,5,27 It has also been reported that there is a decrease in renal perfusion in kidney following SWT procedure by using dynamic gadolinium-DTPA enhanced magnetic resonance imaging. 27 Studies focused on two possible explanations for the impairment of renal flow; renal sympathetic nerves may be activated by shock waves and vasoconstriction may be occurred by vasoconstrictors released from kidneys in response to the shock waves. As a result of this transient ischemic insult, it is thought that free oxygen radical Figure 2.…”
Section: Discussionmentioning
confidence: 98%
“…Several clinical studies, measuring renal resistive index or followed renal blood velocity in the kidney subjected to SWT, showed that an increase in resistive index or a reduction in blood velocity indicative of vasoconstriction occurred. 4,27,28 It has also been reported that there is a decrease in renal perfusion in kidney following ESW procedure by using dynamic gadolinium-DTPA enhanced magnetic resonance imaging. 27 Studies focused on two possible explanations for the impairment of renal flow; either renal sympathetic nerves may be activated by shock waves or, alternatively, the vasoconstriction may be secondary to vasoconstrictors released from kidneys in response to the shock waves.…”
Section: Discussionmentioning
confidence: 99%
“…4,27,28 It has also been reported that there is a decrease in renal perfusion in kidney following ESW procedure by using dynamic gadolinium-DTPA enhanced magnetic resonance imaging. 27 Studies focused on two possible explanations for the impairment of renal flow; either renal sympathetic nerves may be activated by shock waves or, alternatively, the vasoconstriction may be secondary to vasoconstrictors released from kidneys in response to the shock waves. As a result of this transient ischemic insult, it is thought that oxygen free radical generation due to ischemia/reperfusion injury may take place, which further contribute to parenchymal damage by lipid peroxidation and disruption of cellular membranes.…”
Section: Discussionmentioning
confidence: 99%
“…Preliminary data were obtained in a small number of subjects (n ϭ 6) undergoing extracorporeal shock wave lithotripsy (ESWL), which results in a physical shock to the renal parenchyma in the vicinity of the focal point (92). Figure 2 illustrates the signal intensity vs. time changes observed in the renal parenchyma following the bolus injection of Gd-DTPA.…”
Section: Techniques Based On Endogenous Contrast Mechanismsmentioning
confidence: 99%